NiCo2O4 nanostructures loaded onto pencil graphite rod: An advanced composite material for oxygen evolution reaction. (1st February 2022) - Ibupoto, Zafar Hussain; Tahira, Aneela; Shah, Aqeel Ahmed; Aftab, Umair; Solangi, Muhammad Yameen; Leghari, Jaleel Ahmed; Samoon, Abdul Hanan; Bhatti, Adeel Liaquat; Bhatti, Muhammad Ali; Mazzaro, Raffaello; Morandi, Vittorio; Abro, Muhammad Ishaq; et al.
Abstract: Driving oxygen evolution reaction (OER) at extremely low overpotential and the blockage of oxygen gas inside the catalytic material leads to the deactivation of catalytic activity, therefore it is an essential step in electrochemical energy conversion systems, but still very challenging task. The clay minerals including bentonite and kaolinite are rich with plenty of active centers and favorable chemical composition for the catalysis applications but limited by the insulating properties, thus they cannot be used as an electrode material for the water splitting. The unique presence of clay minerals in the form of pencil graphite rod (PGR) and its attractive architecture enabled us to exploit advantageous features and use them as an in situ electrode for growth of metal oxide nanostructures for the electrolysis applications. The naturally inherent presence of SiO2 favors the catalytic properties and durability of the electrode whereas the MgO produces the abundant oxygen vacancies and Co 3+ ions for OER process. Herein, we present a facile approach of using PGR as host substrate and co-catalyst for the loading of Co3 O4, NiCo2 O4 and NiO nanostructures and the modified electrode carried high porosity for easily bubbling of oxygen gas, plenty of intrinsic active centers coming from both clay minerals and metal oxides for excellent OER process. The fabricated electrode is physically well-characterized, and it has a natural ability to sustain a long term stability even at higher current densities and industrial electrolyzer conditions. The NiCo2 O4 /PGR, Co3 O4 /PGR, and NiO/PGR electrodes exhibit an overpotential of 234, 242 and 272 mV respectively at a current density of 100 mAcm −2 in 1.0 M KOH electrolytic solution. The presence of large number of oxygen vacancies through SiO2 and MgO, high Ni 2+ /Ni 3+ and Co 3+ /Co 2+ ratios, multi metal centers, large specific surface area, high pore volume, high electrochemical active surface area and fast charge transport within the NiCo2 O4 /PGR are the main reasons for its superfast OER kinetics. Thus, the proposed method of electrode design will pave a potential way for high performance electrochemical devices like metal air batteries, fuel cell and supercapacitors. Highlights: Metal oxide nanostructures were decorated on graphite rod electrodes. MgO and SiO2 played a dynamic role towards efficient oxygen evolution reaction. The deactivation of electrode was prevented due to the porosity. The NiCo2 O4 /PGR exhibits an overpotential of 234 mV at 100 mAcm −2 . The fabricate electrodes were found durable for 60 h.